The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1108/03074801211244940
|View full text |Cite
|
Sign up to set email alerts
|

Social media at the university: a demographic comparison

Abstract: PurposeThe purpose of this paper is to examine faculty and student responses to questions regarding their use of social media and to determine possible demographic differences.Design/methodology/approachA web‐based quantitative survey format utilizing multiple choice and matrix type questions was selected for this research.FindingsBoth faculty and students are active users of social media. Some distinct demographic differences were found but they did not always match expected results.Research limitations/impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 12 publications
7
43
2
Order By: Relevance
“…Every faculty member, regardless of gender or academic rank, who responded to the survey, seems to be in general agreement concerning the pros and cons of using social media in the classrooms. While some research has supported the argument that there is a difference between the genders when it comes to the use of technology and the Internet, and more specifically, social media (Agbatogun, 2013;Huang et al, 2013;Ruleman, 2012), this study did not find evidence to support that finding. However, this study does concur with Kim et al (2011) andAgbatogum (2013), who found no significance relation between the use of social media, gender and academic rank.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Every faculty member, regardless of gender or academic rank, who responded to the survey, seems to be in general agreement concerning the pros and cons of using social media in the classrooms. While some research has supported the argument that there is a difference between the genders when it comes to the use of technology and the Internet, and more specifically, social media (Agbatogun, 2013;Huang et al, 2013;Ruleman, 2012), this study did not find evidence to support that finding. However, this study does concur with Kim et al (2011) andAgbatogum (2013), who found no significance relation between the use of social media, gender and academic rank.…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, it seems that females are more likely to use communication social tools (e.g., Facebook) than males as reported by Rovai and Baker (2005) and Ruleman (2012). Ruleman also found, contrary to traditional thought, that older faculty (61+), both male and female, use social media more than the middle-aged group (45-60).…”
Section: The Role Of Gender and Academic Rank In The Use Of Social Mediacontrasting
confidence: 36%
See 1 more Smart Citation
“…International Journal of Instruction, April 2018 • Vol.11, No.2 were some research findings contradicted this result, Ruleman (2012) suggested that females are more likely to use communication social tools (e.g., Facebook) than males. It is clear from Table 4 that there was a significant difference in the scores for undergraduate and postgraduate students for MSNAs usage in social life (t=-3.35, p<0.05) in favour of postgraduate students.…”
Section: International Journal Of Instruction April 2018 •mentioning
confidence: 44%
“…Firstly, and with regard to motivations for using Facebook, social relationships were the most important motivation for use, followed by entertainment Hussain, Gulrez, & Tahirkheli, 2012;Moradabadi, Gharehshiran, & Amrai, 2012). Secondly, and in relation to frequency of use, a large proportion of students used Facebook on daily basis or logged in several times a day (Hrastinski & Aghaee, 2012;Hussain et al, 2012;Ruleman, 2012). The minimum time spent on site was 10 minutes, while the maximum time was 100 minutes (Kalpidou, Costin, & Morris, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%